Analyzing the Antecedents of Tourist Loyalty: A Multi-Group Analysis of Gender Differences - Dewi, Putu Eva Silvia; Hapsari, Raditha Dwi Vata; Yulianti, Ida (Jurnal Aplikasi Manajemen, 2025)
Bali, a province in Indonesia, is a highly sought-after travel destination for both domestic and international tourists, renowned for its vibrant culture, diverse natural landscapes, and an array of captivating man-made attractions. However, Karangasem Regency, despite its beautiful offerings, has the highest poverty rate in Bali. The tourism sector has great potential to enhance the quality of life for local residents. The objective of this study is to examine the impact of authenticity on visitor loyalty within the cultural tourism sector of Karangasem Regency. The involvement of memorable tourism experiences and destination image variables in this study is expected to contribute to tourism growth and drive the Indonesian economy. A quantitative approach with the PLS-SEM method was used to analyze data from 353 respondents. Multi-group analysis was used to identify the moderating effect of gender differences in this study. The results of this study show that authenticity has a positive and significant influence on tourist loyalty. Memorable tourism experience and destination image can mediate the relationship between authenticity and tourist loyalty. Surprisingly, gender differences do not significantly influence the relationship between authenticity and tourist loyalty. Both females and males have the same perception of cultural tourism in Karangasem. Theoretically, this study can enrich the literature on tourist loyalty in cultural tourism with a comprehensive construct accompanied by the moderation of gender differences. Practically, this study can serve as a reference for tourism managers to develop sustainable tourism that benefits the community's welfare and generates profit.